Prevalence of obesity and association between body mass index and different aspects of lifestyle in medical sciences students: A cross‐sectional study - Armin Aslani; AmirReza Faraji; Bager Allahverdizadeh; Azita Fathnezhad‐Kazemi (Wiley, 2021)
Abstract Aim The global obesity pandemic is a major health problem with adverse effects on physical and mental health. The aim of this study was to investigate the prevalence of obesity and the association between BMI and different aspects of lifestyle. Design A cross‐sectional study. Methods Data collected from 380 medical sciences students using demographic characteristics and Eating Behavior, Physical Activity and Perceived Stress Questionnaires were analysed using descriptive and inferential statistics, namely analysis of variance (ANOVA), t test, Pearson's test and multivariate linear regression model. Results The prevalence of obesity and overweight was 3.2% and 25.3%, respectively. There was a positive and significant statistical association between emotional eating (r = .542), extrinsic eating (r = .488) and perceived stress (r = .489) with BMI, also significant and an inverse association was obtained between emotional eating (r = −.488) and total physical activity score (r = −.394) with BMI. Factors such as sex, total physical activity score and leisure time activity, external eating behaviours, emotional eating, restricted eating and perceived stress had a significant role in explaining BMI changes. Conclusion There is a need to develop interventions to improve dietary behaviours, management stress and access to sports facilities by health‐promoting activities and the provision of online health resources.